The reality of social construction / Dave Elder-Vass. - Elder-Vass, Dave (Cambridge University Press, 2012)
"'Social construction' is a central metaphor in contemporary social science, yet it is used and understood in widely divergent and indeed conflicting ways by different thinkers. Most commonly, it is seen as radically opposed to realist social theory. Dave Elder-Vass argues that social scientists should be both realists and social constructionists, and that coherent versions of these ways of thinking are entirely compatible with each other. This book seeks to transform prevailing understandings of the relationship between realism and constructionism. It offers a thorough ontological analysis of the phenomena of language, discourse, culture, and knowledge, and shows how this justifies a realist version of social constructionism. In doing so, however, it also develops an analysis of these phenomena that is significant in its own right"--